Implementation of a care coordination system for chronic diseases - Sukaina Abdulghani Abdulali Akhdar; Fatima Abdulgani Abdulali Akhdar; Merfat Hassan Ali Al Matter; Zahra Mansour Ahmad Alsinan; Majedah Ahmad Ali Alrabie; Zahra Mohammad Ali Al-Tarouti; Zahra Salman Ibrahim Al-Qarnat; Asrar Mohammed Saeed Al Abdulwahab; Fatimah Jassim Abdullah Juleh; Roqaia Mohammed Saeed Hassan Al Abdulwahab; Mohammed Fouad Alibrahim; Sabri Youseff Alsandal; et al. (International Journal of Scientific Research and Innovative Studies, 2022)
The prevalence of chronic diseases has been steadily increasing, but the management indicators for these conditions have not shown significant improvements. This paper proposes a new policy to enhance the existing chronic disease management system. The policy includes the establishment of care plans for patients with hypertension and diabetes by primary care physicians, as well as the provision of care coordination services based on these plans.